Evaluation of Risk Factors for Development of Pulmonary Hypertension in Patients with End Stage Renal Disease Undergoing Hemodialysis - Ali Hussein Fadhil; Hashim Mahdi Hashim; Arif Sami Malik; Jawad Kadhum Manuti; Moayed Basheer Hamid (Diyala Journal of Medicine, 2023)
Background: Pulmonary arterial hypertension (PAH) has recently been identified as a common complication in patients with end-stage renal disease (ESRD) who are undergoing hemodialysis (HD) or peritoneal dialysis (PD). The risk factors for the development of PAH in those patients are not well understood.